The Role of Victimology in the Protection of Crime Victims in Indonesian Criminal Justice System - Yunara, Edi; Kemas, Taufik (Mahadi: Indonesia Journal of Law, 2024)
Crime victims often find themselves in a consistently disadvantaged position, suffering physically, psychologically, and materially due to the crimes they endure. Unfortunately, the state's attention to victims lacks the intensity given to criminals, with a predominant focus on the legal position and human rights of offenders. Striking a balance between justice for perpetrators and protection for victims is essential. Presently, victims are predominantly considered supplementary to the sufferer, serving as witnesses solely to establish the guilt of the perpetrator. This research uses legal normative methods and employs a descriptive-analytical approach to explore victim guarantees in the Indonesian criminal justice system. The study scrutinizes statutory regulations, emphasizing the role of victimology in safeguarding crime victims. Historically, victim protection primarily centered on the right to compensation. However, Law Number 13 of 2006 concerning Witness and Victim Protection, in conjunction with Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Witness and Victim Protection, significantly expanded victims' rights. Despite this progress, the integration of victim rights into the criminal justice system remains incomplete. The Indonesian criminal justice system must prioritize and safeguard victims' interests, acknowledging the crucial role of victimology in advocating for the rights of those harmed by perpetrators.